Third World: A Definition - Gonzales Casanova, Pablo (Kasarinlan: Philippine Journal of Third World Studies, 2007)
Coined at the end of the Second World War, the term "third world" has since then been used to denote a complex of intersections That makes it possible to allude to a single vaguely-defined phenomenon. At times used for the most diverse purposes and meanings, and yet also rejected for ideological and scientific reasons, the coinage expresses a category of nations with considerable differences. The common thread though appears to be the intent to group peoples of colonial origin or those who, having lived a history of colonialism, were burdened with the new forms of colonialism and dependence. New developments in the global order, however, seemed to have contributed to the deterioration and relative disuse of the expression. Wit a revival of the center-periphery discourse and the North-South dichotomy, the usage of the term continues, albeit this time with fewer ideological discriminations and more vagueness.